About the Dictionary of the Cheboksary Regional Speech of the Russian Language - Eduard V. Fomin; Tamara N. Erina (Этническая культура, 2020)
This work is devoted to the discussion of the problems associated with the compilation of the the Russian language dictionary of the Cheboksary region speech. The purpose of the work is to consider the macro- and microstructure of the dictionary of speech of the residents of Cheboksary and the agglomeration. The authors use traditional methods of linguistics: descriptive, comparative, contrastive. The article is based on the materials of the designed dictionary, which, in turn, were collected in the course of many years of observation of the speech of the Cheboksary residents in natural conditions. The reaserchers come to a conclusion that he Cheboksary regiolect is an example of a self-sufficient collective idiolect, possessing stable specific uses of literary units of the Russian language. These units can exist not only in the form of published systematized lists or databases, they can also be lexicographic. Presenting the material as a separate vocabulary gives it more weight than publications in the form of small genres. Lexicography offers non-traditional urbanonyms, specific stable phrases and sentences, chuvashisms, which in general can be called cheboksarisms. In a dictionary entry, the required elements are the lemma and its interpretation. At the same time, such elements as transcription of the headword and chuvashism, etymological information, illustrative material can be activated in its composition as needed. By and large, the dictionary is intended not only to provide a scientific understanding of the Cheboksary region, but also to serve as an assertion of the region's self.